Effect of exergames on physical function, cognitive capacity, depressive state and fall-risk in Mexican older adults: A pilot study - Gómez Miranda, Luis Mario (2019)
Introduction: By the year 2050, the Mexican older adult population rate will triple, and consequently, there will be an imperative need to offer to this aging group a better quality of life, including maintaining their functional and cognitive autonomy. Purpose: To determine the effects of exergames on physical function, cognitive capacity, depressive state and fall-risk in Mexican older adults. Methods: In a quasi-experimental design, 14 older adults were divided into an experimental (EG, n = 7) and a control (GC) group. Exergames and physical conditioning exercises were performed for 15-weeks by participants in the EG. Measures of physical function (Senior Fitness Test, SFT), cognitive capacity, depressive state, and fall-risk were obtained before and after the intervention. Dependent variables were analyzed by general linear-model ANOVA tests (2 groups x 2 measurements). Results: Significant interactions were found between groups and measurements in SFT upperbody flexibility (p = 0.041) and agility scores (p = 0.007). The EG reduced pre- to post-test agility times (7.71 ± 1.54 vs. 6.39 ± 1.78 s, p = 0.010). Conclusions: Physical activity in combination with exergames is a feasible and effective strategy to improve flexibility and agility in older adults. The use of technologies is an attractive and effective tool to promote health and avoid physical deterioration in Mexican older adults.